Sociology Subject Teacher's Strategy in Overcoming Students' Social Loafing in Surakarta - Kristy, Grisyelda Tabitha; Budiati, Atik Catur (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to find out the teacher's strategy for overcoming social loafing in students in sociology subjects that occur in high schools. This research discusses the causal factors, impacts, and methods of sociology teachers in overcoming the phenomenon of social loafing in Surakarta high schools. The study used a qualitative approach with a phenomenological research type. Data sources come from informants, observation results, and documentation. Informants involved 10 students in grades X and XI, two sociology teachers, and observations of the school environment. Observations were made by observing the learning process of sociology teachers in the classroom—research documents in the form of photos and recordings of research interviews. Test the validity of the data using the source triangulation method by comparing all data. Data analysis using the Miles & Hubberman technique includes reduction, data presentation, and conclusion drawing. The results showed that the causes of students' social loafing include low learning motivation, group cohesiveness, teacher interpersonal communication, and other external factors. The impact of social loafing consists of an unequal division of tasks in group work, fragile friendships, decreased self-confidence, laziness in learning and schoolwork, and difficulty concentrating. Strategies employed by sociology teachers include identifying individual performance, adopting a variety of learning methods, encouraging interactive communication, paying attention to students who find it difficult to mingle, and collaborating with counseling teachers. Based on this, it can be concluded that students still tend to social loaf, but the strategies pursued by teachers can help them reduce laziness in group work.